Biodegradable soil sealing tape
By using geosynthetic material pads composed of biodegradable materials, combined with the swelling performance of the intermediate fill layer, the problems of material pollution and sealing in the prior art are solved, and the mechanical stability and sealing of the material are achieved, and the mechanical stability and sealing of the material are achieved. Shear strength is provided in sloped terrain.
Patent Information
- Application Number
- CN202380050531.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-21
AI Technical Summary
Existing geosynthetic pads may lead to environmental pollution and reduced sealing after long-term use, and may easily cause slip problems in slope terrain.
The upper cover layer, lower cover layer and connection structure composed of biodegradable materials are adopted, combined with the wetting performance of the intermediate fill layer, and the mechanical stability of the material is achieved through the reduction of peel strength and the control of wetting bulge during the biodegradation process. and sealing.
The long-term mechanical stability and sealing of geosynthetic material pads are achieved, reducing the risk of environmental pollution, and providing shear strength in sloped terrain to prevent slippage.
Smart Images

Figure CN119497666A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a geosynthetic mat, which comprises: an upper covering layer; a lower covering layer; an intermediate filling layer composed of a filling layer material arranged between the upper covering layer and the lower covering layer, wherein the filling layer material comprises a swellable material, wherein the filling layer material has a swelling performance; and a connecting structure, by means of which the upper covering layer and the lower covering layer are mechanically connected to each other at multiple positions through the intermediate filling layer, wherein the connected positions are spaced apart from each other, preferably in positions following each other along a straight line at regular intervals, so that the upper covering layer and the lower covering layer have a peeling strength with each other through the connecting structure. Background Art
[0002] The filling layer material has a swelling property, which is typically characterized by a swelling degree at a predetermined time after the start of the swelling process, which is determined by the ratio of the volume of the filling layer material, including the water absorbed therein, at the predetermined time to the initial volume of the filling layer material, which the filling layer material has before the start of the swelling process, wherein the swelling degree is determined by completely sinking the geosynthetic mat into the water pool in a period of time until the predetermined time and determining the volume of the filling layer material before the sinking and at the predetermined time. The swelling degree thus describes the swelling capacity of the material under unimpeded conditions and can be determined, for example, according to ASTM D5890. Here, for example, a defined amount (2 g) of dry filling layer material is placed in a 100 ml measuring cylinder filled with 90 ml of water. Subsequently, it is filled to 100 ml with water. The filling layer material drops to the bottom and the initial volume of the filling layer material can be read at the scale of the measuring cylinder directly after the filling layer material is filled. The filling layer material then swells for a predetermined duration, for example at least 16 hours. The swelling volume can then be read off by determining the height of the swollen filling material using the scale on the measuring cylinder and the degree of swelling can be determined by taking the quotient with the initial volume.
[0003] Another aspect of the invention is the use of such a geosynthetic mat and a method for producing such a geosynthetic mat.
[0004] Geosynthetic mats of the type described above are used to create a seal on or in a soil layer and, in other cases of application, can also be used to additionally stabilize the soil layer and / or to protect the structure from mechanical or hydraulic influences or a combination thereof, for example in the region of waterways or riverbanks, dams, weirs or dike structures. The geosynthetic mats can also be used to protect other thin-layer sealing components.
[0005] The operating principle of such geosynthetic mats is that the intermediate filling layer, which is typically many times thicker than the upper and lower covering layers, does not expand and does not harden in the state directly after production and thus has a mechanical flexibility that allows the geosynthetic mat to be rolled up. The geosynthetic mat can thus be transported on the one hand, and on the other hand the flexibility enables the geosynthetic mat to be closely fitted to the soil topology at the installation site. The geosynthetic mat is then unfolded at the installation site; in this case, if necessary, by unfolding a plurality of geosynthetic mats side by side in parallel and overlapping, it is also possible to cover soil areas that are wider than the width of the geosynthetic mat transversely to its longitudinal direction corresponding to the unfolding direction.
[0006] After the filling, the intermediate filling layer expands by absorbing water, which can be caused by the soil moisture at the filling location and can be accelerated by artificial water supply. The expansion leads to a homogenization and reduction of the pore volume of the intermediate filling layer, thereby achieving the desired uniform and as isotropic as possible very low water permeability, which is determined by the permeability characteristic value k 10 Characterization, the penetration characteristic value is ideally less than 5×10 -10 and preferably less than 5×10 -11 m / s. However, the homogenization and reduction of the pore volume requires that the intermediate filling layer cannot expand unimpeded, for which the influence of the upper and lower cover layers connected to each other is required as a mechanical counterpressure, thereby causing the desired limitation of the volume increase. In certain filling situations or filling phases, this counterpressure can also be caused or intensified by the surface pressure on the upper cover layer, which is achieved by the soil layer filled above the geosynthetic mat via its gravity. The low water permeability achieved leads to a sufficiently high sealing effect, so that water in static or flowing water bodies can be retained, landfill sealing can be provided or dam constructions can be protected from moisture penetration.
[0007] Thus, the upper and lower covering layers and the connecting structure connecting the two covering layers to one another fulfill the essential functions required for the use and properties of the geosynthetic mat. Thus, by means of the covering layers and the connecting structure, the geosynthetic mat can be rolled up and handled, so that even when rolled up after production, during transport and when laid at the installation site, the geosynthetic mat retains its structure with the desired thickness with the intermediate filling layer positioned between the two covering layers. By means of the two covering layers and the connecting structure, a mechanical counterpressure is also generated and maintained after the installation of the geosynthetic mat, which counteracts the swelling pressure of the intermediate filling layer, so that the intermediate filling layer exhibits the desired, tight structure when expanded. By means of the expansion under the mechanical counterpressure achieved by the intermediate filling layer being constrained between the two covering layers and the connecting structure, the inventors have learned that, for the first time, the desired low permeability of the geosynthetic mat after the expansion of the intermediate filling layer can be achieved, and this low permeability should in the best case be achieved independently of whether a layer with a certain weight can be installed above the geosynthetic mat.
[0008] Finally, in the case of installation of geosynthetic mats of the type described above, for example, obliquely on a slope, the geosynthetic mat must have shear strength in order to prevent the geosynthetic mat itself from being or forming an unstable layer in the slope, so that slope slippage could occur with the geosynthetic mat as a separating layer. The shear strength is achieved by the connection between the upper and lower covering layers, thereby achieving a stable connection between the lower soil layer on which the lower covering layer lies and the upper soil layer lying on the upper covering layer.
[0009] Geosynthetic mats of the aforementioned type with good sealing, shear strength and mechanical load-bearing properties are known as clay sealing strips, for example as bentonite mats from Naue GmbH & Co. KG and are described in EP 0 278419 B1.
[0010] From DE 199 56 783 A1 a mat is known which is designed to cover a corpse and which is developed from the bentonite mat described in EP 0 278 419 B1. In the modified mat, a mat is proposed by using a bactericidal or antiseptic powder instead of a powder having a sealing effect (e.g. bentonite), which effectively prevents active microorganisms from escaping from the burial site by a chemical-biological effect. The mat thus developed proposes an alternative to providing a chemical-biological barrier against microorganisms by means of an expanded seal, in that a corresponding bactericidal / antiseptic filler is used. This is a special mat suitable for the specific purpose of covering corpses and the attendant microbiological hazards, which, however, cannot be used well for other purposes.
[0011] Another soil mat is known from DE60203517T2, which is based on the technology known from EP0278419B1. In the soil mat, it should be realized that the bentonite arranged in the middle layer can enter the cavities and gaps in the adjacent soil area and expand there. Thus, the cavities and gaps should be filled. In order to achieve the above content, the cover layer of the soil mat should be dissolved by water when in contact with the soil. The technology of the soil mat therefore abandons the principle of the soil mat with the swelling and compression function of the bentonite in the middle layer described in EP0278419B1 at first, and instead strives for the rapid dissolution of the cover layer, whereby the bentonite can move from the middle layer to the cavities and gaps in the adjacent soil before it starts to swell and then expand there. The soil mat is therefore suitable for specific applications, in which the soil layer that is constructed in principle by a sealing soil material but has cavities and gaps should be sealed in the manner of: sealing the above defects. Due to the rapid dissolution of the cover layer required for this, the soil mat is not suitable for other general sealing applications.
[0012] This known geosynthetic mat is installed for temporary or permanent sealing, and in addition, for example, for protecting thin layers of synthetic film, as an element with separation function or for stabilizing soil layers or surfaces. However, in some applications with variable geometry, from the perspective of environmental protection, adverse effects may occur in the long term. Therefore, on the one hand, when using this geosynthetic mat permanently, sections of the geosynthetic mat may be separated by corrosion processes and carried to other locations by wind or water flow and then cause pollution in undesirable places. When using this geosynthetic mat temporarily, although in some cases the geosynthetic mat can be removed from the soil again in isolation and then removed. However, in many cases, this isolated removal is not feasible because the soil layer adheres to the geosynthetic mat or damages the geosynthetic mat when removed. In this case, a large amount of soil is usually removed together and all removed volumes must be removed later. Due to the artificially synthesized components in the removed volume, the removal belongs to a high level of pollutants and is correspondingly costly. Summary of the invention
[0013] The object underlying the present invention is to provide a geosynthetic mat which overcomes the above-mentioned disadvantages and in doing so comprises at least the necessary mechanical and sealing properties of the known geosynthetic mats, preferably exceeds them.
[0014] The object is achieved according to the invention by means of a geosynthetic mat of the type mentioned at the outset, wherein the upper covering layer and / or the lower covering layer consists of a biodegradable material or comprises a biodegradable material, wherein the peel strength at a predetermined time after the onset of the biodegradation process is characterized by a residual peel strength degree, which is formed by the square of the quotient of the reduced peel strength and the initial peel strength, wherein the upper covering layer and the lower covering layer and the connecting structure have the reduced peel strength at the predetermined time, and the upper covering layer and the lower covering layer and the connecting structure have the initial peel strength before the onset of the biodegradation process, wherein in a composting test the geosynthetic mat is completely placed in fertilizer and composted in a temperature range of above 25° C. and below 65° C. until the predetermined peel strength is reached. The peel strength is measured at a predetermined time before the insertion and after the removal from the fertilizer in a peel test, or in an ocean incubation test (with the following environmental conditions: temperature 30°C + / - 2°C; aerobic conditions in seawater with a salinity of 3.5% by weight + / - 1% by weight), and in a peel test the peel strength is measured at a predetermined time before the insertion and after the removal from the seawater, the degree of residual peel strength is determined, and wherein the swelling behavior is characterized by a swelling bulge, which is formed by the quotient of the volume of the filling layer material together with the water absorbed therein at a predetermined time and the initial volume of the filling layer material before the start of swelling, wherein the swelling bulge is obtained by completely immersing the filling layer material layer in a water pool and loading the filling layer material layer with 4.5 N / m 2 According to the present invention, the geosynthetic mat has a swelling-degradation ratio formed by dividing the swelling ridge by the residual peel strength, which is in the range of 1 to 5 in the first week after the swelling process and the biodegradation process start simultaneously and in the range of 1.5 to 25 at each predetermined time from the second month to the end of the third month after the start of swelling and degradation, preferably in the range with a lower limit of 2 and / or an upper limit of 15.
[0015] The invention is based on the following recognition: The invention is based in principle on the concept of at least partially, preferably completely replacing the synthetic components of the geosynthetic mat, which are in particular inevitably used in the previous geosynthetic mats to provide the upper and lower covering layers and the connecting structure, by biodegradable materials, in that the upper and lower covering layers and the connecting structure comprise biodegradable materials or consist of such biodegradable materials. "Biodegradable materials" in the sense of the invention are to be understood as materials that, under typical environmental conditions in a soil filling layer, i.e. in a moist environment of a soil layer which can consist of the main components soil, sand, clay and a mixture of the typical soil layer components, decompose in a biological, chemical or biochemical process and thus become environmentally friendly components in a short or medium term, which is understood to be a period of weeks to months, up to two or more years, for example up to 10 years.
[0016] The reduction of the peel strength which is decisive according to the invention by the biodegradation process is determined according to the invention in a composting test, which can be determined, for example, by
[0017] - Soil composting tests with the following environmental conditions: temperature 50°C + / - 5°C; thermophilic conditions according to ISO16929, or
[0018] - passed the marine incubation test with the following environmental conditions: temperature 30°C + / - 2°C; aerobic conditions in seawater with a salinity of 3.5 wt% + / - 1 wt%;
[0019] It is to be understood that when the material used according to the invention is intended for soil sealing outside flowing or stationary bodies of water, the material has in particular a biodegradability according to the soil composting test mentioned above, and when the material used according to the invention is intended for soil layer sealing in or at a body of water, the material has a biodegradability according to the marine incubation test mentioned above. The peel strength of the biodegradable material is determined here in the biodegradation time period, so that the geosynthetic mat is stored under the above-mentioned environmental conditions tested in one of two suitable tests for a plurality of different specific durations and after the duration is subjected to a peel test, for example a roller peel test according to DIN 53295 or a peel test according to DIN EN 28510-1:2014DE or according to ASTM D6496, in order to thereby determine the time course of the peel strength.
[0020] In this case, in particular a composting environment according to Section 5.1 of DIN EN ISO 16929:2018-04 can be provided, ie an environment having the following conditions in order to carry out the composting test:
[0021] - placing the geosynthetic mat in fresh biowaste with natural, ubiquitous microflora, so that the biowaste covers the geosynthetic mat with a thickness of at least 30 cm on both sides,
[0022] -Monitoring of temperature, pH, water content and gas composition,
[0023] - Carry out composting tests in containers that are large enough so that natural self-heating occurs, with sufficient and uniform aeration through the air delivery system,
[0024] - the container can be carried out in a climate chamber with a constant chamber temperature,
[0025] - When fertilizers reach temperatures above 65°C during the spontaneous thermophilic phase, the diversity of microorganisms can be reduced.
[0026] - In order to restore the full bandwidth of thermophilic bacteria, the fertilizer can be re-inoculated with mature fertilizer (approximately 1% of the total initial mass of biowaste) from a more recent source (up to 3 months).
[0027] Here, homogeneous biowaste of the same age and origin is used for the composting test, which is reduced to a particle size of up to 50 mm by crushing or sieving. Depending on the type of waste, 10% to 60% of filler consisting of structurally stable components such as sawdust or bark with a particle size of 10 mm to 50 mm is added. The biowaste must meet the following criteria:
[0028] - the C / N ratio of the mixture consisting of fresh biowaste and filler is between 20 and 30, which can be equalized with the aid of urea as required,
[0029] - The water content is greater than 50% by mass, but there is no free water
[0030] - the ignition loss of the dry residue is greater than 50% by mass,
[0031] - pH value is above 5.
[0032] In addition to the peel strength, according to the invention, the swelling behavior is also considered as a property of the geosynthetic mat and is set in relation to the peel strength. According to the inventors' knowledge, the pure swelling degree cannot be considered as a characteristic variable for many applications with regard to the desired long-term sealing properties of the geosynthetic mat, because the desired compression properties of the intermediate filling layer cannot be adequately described by the swelling degree. Instead, the intermediate filling layer is formed or characterized by a swelling bulge, which describes the volume increase under a constant pressure, which is achieved during the test as a contact pressure applied to the material layer, for example by a plate or disk with a corresponding weight.
[0033] In principle, it is understood that the swelling and swelling are taken into account for at least the first month and the following two months. In principle, the swelling and swelling can also be taken into account for a longer period of time, which results in a good coordination of the properties, especially in the case of slowly swelling intermediate filling layers. In the case of some materials, it should be taken into account that the material has already undergone an initial swelling due to storage in the air, for example because the material is very dry and has the ability to absorb water during the production process. In this case, it is understood that the material is used in the test according to the invention for the swelling and swelling properties only in the state that occurs later, in the actual conditions of temporary storage in the air and in the swelling that occurs, in order to avoid distortion of the results due to non-representative initial effects that could otherwise occur in the first hours or days of the swelling and swelling test.
[0034] The key to achieving the function of the geosynthetic mat is that sufficient counterpressure is always maintained by the upper and lower covering layers and the connecting structure against the expansion of the middle filling layer, which counterpressure leads to sufficient compression of the middle filling layer and thus closure of the pores in the middle filling layer in a timely manner, especially in the first few months. The necessary tightness is thus achieved and can then be maintained over a long period of time, especially after the expansion has gradually approached the maximum swelling and the biodegradation has progressed to the point where the peel strength has significantly decreased or is close to zero.
[0035] On the other hand, in many applications it is important that the geosynthetic mat provides mechanical properties that prevent slippage when a slope layer is inserted at any time after its installation. For this purpose, according to the inventors' knowledge, an initial small reduction in the peel strength is decisive compared to the expansion in order to maintain the shear strength by the biodegradable structure in the early stages before the stabilizing function of the intermediate filling layer is formed.
[0036] The time period within which the desired properties characterized by the swelling-degradation ratio must prevail may range from a few weeks to one or two years from the start of swelling and biodegradation.
[0037] Although the use of such biodegradable materials can in principle reduce or completely avoid the problem of contamination dispersion or contamination in such geosynthetic mats after removal, the use of such biodegradable materials is hampered by the fact that the sealing effect of the geosynthetic mat cannot be achieved in principle due to biodegradation, since the required counterpressure is not generated or is not generated sufficiently during the expansion of the intermediate filling layer and, as a result, there is an excessively high permeability of the geosynthetic mat after expansion, which does not achieve the desired sealing function. On the other hand, the shear strength of the geosynthetic mat is greatly reduced by the biodegradation of the cover layer and the connecting structure, so that when the geosynthetic mat is installed obliquely in the slope layer, the slope layer slips. Therefore, the use of biodegradable geotextiles is considered critical or unsuitable in many applications with regard to the time requirements for the mechanical bonding effect, and DIN EN 12225 specifies test standards for geosynthetics in order to verify the general resistance to microbial degradation.
[0038] The geosynthetic mat according to the invention overcomes the problem by a swelling behavior that is coordinated in time with respect to the characteristics of biodegradation. To this end, the composite consisting of the upper and lower covering layers and the connecting structure is characterized according to the residual peel strength degree, which the composite has in the following time period due to the biodegradation rate after a specific biodegradation duration, i.e., at a predetermined time after the start of the biodegradation process. Therefore, the residual peel strength degree characterizes the composite consisting of two covering layers and the connecting structure as follows: how quickly its peel strength decreases over time through the biodegradation process, that is, a curve that depicts the peel strength of a biodegradable material over the time of biodegradation. The slope of the curve at each position at any time can be defined as the peel strength reduction. The further the biodegradation advances, the smaller the peel strength reduction. The faster the biodegradation occurs, the steeper the curve of the peel strength reduction over time decreases, and thus the faster the peel strength of the composite decreases. The reduction in the degree of reduction in the peel strength can be achieved by biodegradation of the upper covering layer, the lower covering layer and / or the connecting structure or by a reduction in the fastening strength of the connecting structure in the upper or lower covering layer.
[0039] On the other hand, the filling layer material of the middle filling layer has swelling properties, which are characterized by the water absorption and swelling ability of the filling layer material. The swelling ability is characterized by swelling swell degree, which describes the swelling swell degree of the filling layer material at a specific moment after the swelling starts compared to the dry volume of the filling layer material before the swelling starts at 4.5 N / m 2The volume increase under the pressure load is measured and a curve is obtained during the time variation process to depict the increase in the volume of the filling layer material during the swelling time. The higher the swelling ridge, the stronger the performance of the filling layer material in expanding under load. It should be understood here that the swelling ridge of the material is determined without path restrictions on the swelling movement, that is, the material can increase its water content or its volume without hindrance when determining the swelling ridge. In practice, this can be carried out by force-controlled tests or by laying a vertically freely movable plate with a weight of 4.5 kg per square meter on the filling layer material when determining the swelling ridge.
[0040] The swellable material of the middle filling layer and the biodegradable material of the upper and lower covering layers and, if applicable, the connecting structure are now designed such that the ratio between the swelling elevation of the swellable material and the degree of residual peel strength of the composite consisting of the upper and lower covering layers and the connecting structure is in the range between 1 and 5 in the initial period of one week and from the beginning of the second month to the end of the third month is between 1.5 and 25, preferably between 2 and 15. The two temporally sequential and coordinated material properties of the middle filling layer on the one hand and of the mechanical composite surrounding the middle filling layer on the other hand ensure that, in the initial phase of the expansion of the middle filling layer, the upper and lower covering layers and the connecting structure between the two covering layers form a sufficiently high mechanical counterpressure that resists the swelling pressure and can be maintained for a long period of time, so that sufficient compression of the middle filling layer occurs during the swelling process. Furthermore, it is achieved that the upper and lower covering layers and optionally the connecting structure are already biodegraded at a later point in time when the swelling is substantially or completely completed and thus no contamination can occur when the geosynthetic mat is removed or when parts of the geosynthetic mat are dispersed due to corrosion.
[0041] According to the knowledge of the inventors, when the pore volume is sufficiently homogenized and reduced, the intermediate filling layer can overall exhibit a shear strength which is at least in the range of the shear strength of the geosynthetic mat directly after installation, i.e., at the initial peel strength of the unswollen intermediate filling layer and the composite of the upper and lower covering layers and the connecting structure, or even exceeds this range. The risk of slipping of the slope due to unstable layer planes in the shaping of the geosynthetic mat is thereby reliably prevented.
[0042] The geosynthetic mat according to the invention achieves a sufficiently high tightness due to the achievable compression by the ratio of the components and material properties with regard to the swelling behavior of the intermediate filling layer and the elimination of the mechanical properties of the upper and lower covering layers, while at the same time avoiding the risk of slipping of the slope and providing the desired hydraulic and mechanical properties in the medium or long term without the contamination that accompanies this. Thus, the geosynthetic mat according to the invention can be installed without local environmental loads and the risk of environmental damage by corrosion and spreading to other locations, and can be removed and disposed of cost-effectively during temporary use, provided that the intermediate filling layer is made of a correspondingly environmentally friendly material or consists of such a material.
[0043] By maintaining the range according to the invention for the ratio between the swelling elevation and the residual peel strength within the first three months, a balanced development of the sealing properties of the geosynthetic mat resulting from swelling and the mechanical strength provided to the soil layer is achieved even when installed in a slope layer and under the influence of corresponding shear forces.
[0044] It is particularly preferred that the swelling-degradation ratio is in the range of between 1.2 and 5 from the third day in the first week after the simultaneous start of the swelling process and the biodegradation process. A particularly preferred swelling-degradation ratio in the first week for the geosynthetic mat to be installed with a soil layer with an applied weight thereon is 1.25 to 4, preferably 1.25 to 3. A particularly preferred swelling-degradation ratio in the first week for the geosynthetic mat to be installed without a soil layer thereon is 1 to 4, preferably 1.2 to 3. In principle, the invention can be preferably implemented for different installation situations in such a way that the swelling-degradation ratio in the first week from the third day is in the following range: the range has a lower limit of 1, or 1.25, or 1.5, or 2 and the range has an upper limit of 1.75, or 2, or 4, or 6.
[0045] Starting from the second month until the end of the third month after the start of swelling and degradation, the swelling-degradation ratio is preferably in a range between 1.75 and 20, preferably in a range with a lower limit of 1.75 or 2 or 2.5 or 3 and / or an upper limit of 25 or 20 or 15 or 10.
[0046] Preferably, the swelling-degradation ratio is in the range between 2 and 50 from the third month until the end of the twelfth month after the start of the swelling process and the biodegradation process, preferably in the range with a lower limit of 3 and / or an upper limit of 30. In this longer period of time, the long-term swelling and degradation process of the geosynthetic mat is detected and the properties of the geosynthetic mat are achieved in such a way that an optimal swelling and degradation behavior is achieved in the longer period of time.
[0047] According to the inventor's knowledge, different effects can be advantageously achieved by such a coordinated reduction of the peel strength on the one hand and the swelling on the other hand. Therefore, a strong weight and volume increase usually occurs at the beginning of the swelling process and a high counterpressure is required to resist the swelling pressure at the time, so as to achieve a structure as close as possible in the intermediate filling layer. The swelling of the intermediate filling layer also causes compression and mechanical stability there, which is obtained by swelling under the counterpressure itself on the one hand, which can be used for a variety of materials of the swellable intermediate filling layer, but also obtains a stabilized intermediate filling layer through a chemical process. Therefore, the layer silicate contained in the intermediate filling layer can be converted into another layer silicate during the swelling process, and sodium bentonite can be converted into calcium bentonite, and thus provide a higher strength and stability relative to shearing forces from the intermediate filling layer itself. The said conversion process in the intermediate filling layer therefore allows that, as the swelling ridge increases, the peel strength of the stabilizing cover layer and the connecting structure is reduced until the cover layer and the connecting structure are completely degraded at a later time.
[0048] A typical example of this is the following intermediate filling layer, which contains or consists of a mineral mixture known as bentonite with the main component montmorillonite in the form of powder or granules. The mineral mixture can be transformed from an initial state containing a sodium-based bentonite portion into an expanded state containing a calcium-based bentonite portion converted therefrom and the shear strength increases in this process. The calcium ions required for ion exchange are usually already contained in the bentonite in sufficient quantities according to the inventor's knowledge, and are always contained in the surrounding soil in additional quantities, which can accelerate the process. Over time, an ion exchange of sodium (monovalent) with calcium (divalent) then occurs, and the environmental conditions determine how quickly the process proceeds.
[0049] It is particularly preferred that the swelling elevation is greater than 1.25, preferably greater than 1.5 or 2 one week after the start of the swelling process and / or the swelling elevation is greater than 1.5, preferably greater than 2 or 3 one month after the start of the swelling process and / or the residual peel strength level is less than 0.95, preferably less than 0.9 or 0.8 three months after the start of the swelling process and / or the residual peel strength level is less than 0.9, preferably less than 0.75 or 0.5 twelve months after the start of the swelling process. In principle, the swelling behavior is to be understood as such that the intermediate filling layer swells to a relevant degree over time, and the biodegradation behavior is to be understood as such that the peel strength decreases to a relevant degree over time. According to the refinement, not only is the ratio of swelling to biodegradation set within a specific range, but the swelling behavior and the reduction of the mechanical strength by biodegradation are also each individually within a favorable value range, which achieves favorable swelling and temporally appropriate biodegradation. For many application purposes, therefore, rapid expansion is initially important in order to establish the tightness, whereas biodegradation can and should preferably take place over a relatively longer period of time.
[0050] It is particularly preferred that the connection structure comprises a needling section between the upper cover layer and the lower cover layer or is formed by such a needling section. In the case of the needling section, by piercing the cover layer with a needle provided with barbs used as a tool, a plurality of individual fibers are pulled from the cover layer through the intermediate filling layer and hooked in the opposite cover layer. Preferably, such needling can be carried out when the pierced cover layer and / or the opposite cover layer are designed as nonwoven layers, i.e. as layers with a disordered fiber structure, from which fibers can be pulled during the needling process and can hook in the opposite layer, so as to form the connection structure. However, needling is also possible when the anchoring cover layer is designed as a cover layer with an ordered fiber structure, i.e., for example a knitted, crocheted or braided cover layer, wherein the needling preferably always starts from the nonwoven layer as the uppermost cover layer, because in the nonwoven layer the fibers have good mobility perpendicular to the layer plane. The needling can in particular provide a connecting structure which connects the upper and lower covering layers to one another at a plurality of points distributed over the surface of the geosynthetic mat and spaced apart from one another, thereby achieving a connection between the two covering layers which acts approximately over the entire surface of the upper and lower covering layers, and which can thus resist swelling pressures and shear forces particularly effectively. If the connecting structure, i.e., the covering layers which are pierced in particular to produce the needling, comprises fibers made of thermoplastics (e.g., PLA, PBS, PBAT), the fibers can be additionally anchored on the rear side of the second covering layer by melting, thereby increasing the initial internal shear bonding force of the geosynthetic mat. This can be done, for example, by means of a flame lance which melts the fiber portions protruding outward from the second covering layer, whereby the fiber portions form nodules which prevent or make it more difficult for the fibers to be pulled out of the second covering layer toward the first covering layer.
[0051] It is further preferred that the upper cover layer and / or the lower cover layer and / or the connecting structure include fibers made of a biodegradable material or are formed by such biodegradable fibers. The design of fibers made of a biodegradable material can achieve, on the one hand, the feasibility of needle punching and good strength, and on the other hand, such fibers can be particularly well biodegraded in a targeted manner and thus provide a desired ratio of swelling ridge to residual peel strength.
[0052] It is further preferred that the biodegradable materials of the upper and lower covering layers are different from each other, or that the biodegradable materials of the upper and lower covering layers are identical. According to the embodiment, in a first design, the biodegradable materials of the upper and lower covering layers are different, which can be advantageous in specific installation situations and soil structures in order to adapt the geosynthetic mat to local requirements on the upper side and the lower side. In many applications, in contrast, the second alternative is advantageous, in which the biodegradable materials of the upper and lower covering layers are identical, i.e. both covering layers are constructed of the same material. The embodiment enables coordinated, homogeneous degradation behavior of the upper and lower covering layers, a beneficial selection of the connection structure between homogeneous materials, and thus is well suited to many applications.
[0053] According to another preferred embodiment, it is proposed that the biodegradable material of the connecting structure is different from the biodegradable material of the upper and / or lower covering layer, or that the biodegradable material of the connecting structure is identical to the upper or lower covering layer. In these two preferred embodiments, in specific installation situations, for example when particularly high shear strengths or shear strengths that act over a long period of time are required, the biodegradable material of the connecting structure can again be different from the biodegradable material of the upper and / or lower covering layer, in order to, for example, achieve a slower biodegradation behavior of the connecting structure than the covering layer or one of the covering layers. In contrast, in many common installation situations, it is again advantageous for the biodegradable material of the connecting structure to be identical to the upper or lower covering layer or both covering layers, so that the production advantages resulting from the same materials are again achieved.
[0054] It is also preferred that the upper cover layer and / or the lower cover layer include a nonwoven layer made of a biodegradable material or are formed by such a nonwoven layer. If the cover layer is formed as such a nonwoven layer or includes such a nonwoven layer, this allows a good adhered support and the shearing force is transmitted from the surrounding soil layer to the civil engineering synthetic material mat, because the nonwoven layer achieves sufficient shearing force transmission to the close soil layer due to its surface structure. The nonwoven layer is also well suitable for needle punching, as previously explained, so that the formation of an efficient connecting structure can be opened. Here, the nonwoven layer should be understood as a fiber layer: the fibers are present in the fiber layer in a disordered manner, and the fiber layer has continuous fibers of medium length in the range of about 6 cm to several meters or more. The nonwoven layer can preferably be composed of fibers with at least two, preferably more different fiber thicknesses, wherein the different fiber thicknesses should be understood as a difference of at least 100%, that is, the following difference, in the case of the difference, the nonwoven layer includes fibers with a first diameter and fibers with a second diameter that is twice as large as the first diameter. By means of such a nonwoven layer with uneven fiber thickness, the biodegradation behavior can generally be well adapted to the swelling behavior of the intermediate filling layer.
[0055] It is further preferred that the upper and / or lower covering layer comprises or is formed by an ordered textile layer of a biodegradable material, in particular a knitted, woven or crocheted textile layer. According to this embodiment, an upper or lower covering layer with an ordered structure of fibers is provided, whereby a higher strength of the covering layer in the longitudinal and transverse directions is achieved, in particular compared to a nonwoven layer, and furthermore, if a dense arrangement of the holes of the fibers in the textile layer is achieved, a generally lower liquid permeability can be achieved.
[0056] It is further preferred that the middle filling layer comprises a mixture of a swellable material, such as bentonite powder, especially sodium bentonite, and a non-swellable additive, such as an inorganic loose material, for example particles, especially sand, glass particles, chalk or coal particles, or is formed by such a mixture. According to the embodiment, a mixture of a swellable material and a non-swellable additive is arranged in the middle filling layer. These two materials are present in the form of loose materials and are preferably uniformly mixed with each other. According to the inventor's knowledge, by adding and mixing such an additive, the load-bearing capacity of the middle filling layer relative to shear forces can be significantly improved, so that after the two covering layers and the connecting structure are basically or completely biodegraded, the mechanical properties of the geosynthetic mat are affected in a favorable manner, so that it is also feasible to install and stay in a steeper slope layer. The mixture can be formed in such a way that it has a proportion of at least 20% by weight of swellable material and at least 20% by weight of additional material, or at least 30% by weight, 40% by weight of swellable material and at least 30% by weight or 40% by weight of additional material.
[0057] It is further preferred that the middle filling layer comprises a hardened or hardening liquid, especially hard oil, such as linseed oil or tung oil, wherein preferably, only in a partial area of the middle filling layer, such as a partial cross section, there is liquid. By adding this hardened or hardening liquid, the mechanical load capacity can be further improved, especially relative to the shear load of the middle filling layer or relative to the mechanical load capacity of the erosion effect acting on the surface, thereby compensating the biodegradation of the cover layer and the connecting structure. Here, the hardened liquid should be understood as a liquid: the liquid is converted from a liquid state to a solid state, for example, by polymer cross-linking or by the evaporation of the solvent portion. And the liquid that causes hardening should be understood as a liquid: the liquid reacts with other components of the middle filling layer, thereby promoting the hardening of the middle filling layer. The liquid can be distributed on the entire middle filling layer and the entire cross section of the middle filling layer, but the liquid can also be applied only in a partial area, for example, in a dotted manner, in a grid belt, a longitudinal belt or a transverse belt of a geosynthetic mat. Similarly, the liquid can also be present only on a partial cross section of the middle filling layer, for example, only in the surface area of the middle filling layer or in the middle area of the cross section of the middle filling layer.
[0058] It is also preferred that the geosynthetic mat is improved by an upper barrier layer arranged adjacent to the upper cover layer and / or a lower barrier layer arranged adjacent to the lower cover layer, wherein each barrier layer is formed by a film, in particular by a film consisting of a biodegradable material, wherein preferably the upper barrier layer is arranged between the upper cover layer and the middle filling layer, the lower barrier layer is arranged between the lower cover layer and the middle filling layer, the upper cover layer is arranged between the upper barrier layer and the middle filling layer, or the lower cover layer is arranged between the lower barrier layer and the middle filling layer. Such barrier layers can prevent swelling-accelerating or swelling-impeding substances from the soil layer adjoining the geosynthetic mat from penetrating into the middle filling layer, thereby adversely and unpredictably influencing the swelling behavior of the middle filling layer. Thus, such barrier layers can achieve a slow swelling behavior due to soil moisture increase or targeted irrigation that is planned and matched to the biodegradation behavior of the connecting structure and the cover layer. Such a barrier layer can be provided by a polyethylene film, but it is also possible to use films consisting of biodegradable synthetic materials for the barrier layer; in particular, biodegradable materials corresponding to the upper or lower covering layer can be used for the barrier layer. The barrier layer can be applied during the production of the geosynthetic mat in the form of a coating (inline extrusion) or as a finished film by lamination, bonding, etc.
[0059] According to another preferred embodiment, the biodegradable material of the upper covering layer, the lower covering layer and / or the connecting structure includes fibers or is composed of fibers, wherein the fibers have a fiber core bundle composed of a first biodegradable material and a fiber core bundle sheath composed of a second biodegradable material that covers the fiber core bundle, wherein the first biodegradable material has a first biodegradation rate, and the first biodegradation rate is higher than the second biodegradation rate of the second biodegradable material. According to the embodiment, the upper covering layer and the lower covering layer and / or the connecting structure contain fibers, wherein the fibers are constructed of a fiber core bundle and a fiber core bundle sheath, wherein the fiber core bundle and the fiber core bundle sheath are constructed of two materials with different biodegradation performances. According to the inventor's knowledge, the design of the fiber achieves the following main advantages: the degradation performance of the fiber, and thus the reduction of its tensile strength, is discontinuously, i.e., in two different degradation stages that follow one another, through this design. Therefore, in the first phase, the fiber core bundle coating first biodegrades, while the fiber core bundle has not yet undergone biodegradation or has only undergone a small amount of biodegradation, because the fiber core bundle coating still protects the fiber core bundle from influences that can cause such biodegradation, i.e., for example, from radiation, liquids. Therefore, in the first phase, the fiber core bundle completely or almost completely retains its mechanical properties, so that if the fiber is mainly characterized by the mechanical properties of the fiber core bundle in terms of its mechanical properties, the fiber does not lose or almost loses its mechanical properties in the first phase of biodegradation of the fiber core bundle coating. After the degradation of the fiber core bundle coating, the fiber core bundle then biodegrades, so that the mechanical properties of the fiber are significantly reduced. In other words, the fiber constructed in this way shows a very delayed reduction in its mechanical properties at first, which then increases at a specific moment. In many cases of application, this is advantageous for the geosynthetic mat according to the invention, since sufficient mechanical strength can be provided by the cover layer and the connecting structure for a certain period of time, which can correspond, for example, to the typical swelling behavior or the typical change behavior of the intermediate filling layer, but after this period of time, a rapid and complete biological degradation of the cover layer and the connecting structure is then achieved together with a corresponding reduction in mechanical strength.
[0060] It is also preferred that the first biodegradable material comprises natural fibers, such as coconut fibers, jute fibers, hemp fibers, bamboo fibers or flax fibers or biodegradable synthetic fibers consisting of PBS, PBAT, PLA or a polymer blend consisting of at least two of these materials, or that the biodegradable material comprises a mixture of a fiber core consisting of natural fibers and synthetic fibers, wherein the weight proportion of synthetic fibers is preferably greater than 30%, in particular greater than 50%. The use of such fiber materials or mixtures consisting of such fiber materials has proven to be particularly suitable for many applications in order to achieve the mechanical strength and biodegradation rate required for geosynthetic mats with swellable materials in the middle filling layer.
[0061] Here, it is further preferred that the second biodegradable material comprises a cellulose-based synthetic material, a starch blend, lyocell, succinic acid (PBS), a biodegradable polyester such as polybutylene adipate terephthalate (PBAT) or polylactic acid (PLA). The material has been proven to be very suitable as a coating material because the material shows sufficiently slow biodegradation performance, but at the same time can be applied well as a coating in a liquid form. It should be understood that the fibers in the coating or the connecting structure can be designed so that the fibers are already coated before the fiber material is processed into the coating, that is, the coating is made of the fibers of the coating. Alternatively, it can also be proposed that the coating is made of uncoated fibers, that is, only fiber core bundles, and then the coating is integrally coated with a second biodegradable material, so as to also cover the cut fiber ends and to achieve reinforcement of the coating by the connecting effect of the second biodegradable material at the intersection of the fibers.
[0062] It is further preferred that the middle filling layer has a -5 Up to 1×10 -9m / s. According to the embodiment, the geosynthetic mat is provided with an intermediate filling layer, which has the following permeability: the permeability is initially insufficient in the production state before installation, so as to achieve a reliable sealing of the soil layer. According to the inventor's knowledge, this permeability can be tolerated or even desired in many applications at first, so as to achieve the penetration of the geosynthetic mat in the first time stage after installation. During the penetration, the particles contained in the water that penetrates the geosynthetic mat accumulate in the intermediate filling layer and cause compression and sealing of the intermediate filling layer according to the form of the blocked filter, that is, a silting process (Kolmationsvorgang) occurs corresponding to the formation of a filter cake in the intermediate filling layer or on the intermediate filling layer. Thus, a favorable sealing effect at a particularly high sealing level can be achieved by means of the particularly low permeability of the geosynthetic mat. Here, in the first stage, the geosynthetic mat only acts as a permeation barrier, and only achieves its final sealing after a certain penetration stage, and then the geosynthetic mat maintains the sealing. According to the inventors' knowledge, the described structure of the geosynthetic mat is particularly well suited for creating a seal in a streambed, such as a stream or river, where liquid flows, and in this case it is used that the liquid in the stream or river carries corresponding particles that can be used for sealing. According to one aspect of the invention, this also includes a geosynthetic strip in which the middle filling layer consists of a material with only a very low swelling capacity or a material that cannot swell, i.e. a material with a swelling bulge of 1 over the entire filling period. Thus, for example, an middle filling layer made of sand or other pourable mineral materials can be used for this sealing effect obtained by silting.
[0063] Another aspect of the invention is a geosynthetic tape, which comprises at least one ply, which comprises or is formed by fibers, wherein the fibers have a fiber core consisting of a first biodegradable material and a fiber core sheath consisting of a second biodegradable material, which sheaths the fiber core, wherein the first biodegradable material has a first biodegradation rate and the second biodegradable material has a second biodegradation rate, which is different from, in particular higher than, the first biodegradation rate of the first biodegradable material. Within the scope of the invention, a geosynthetic tape is understood to be a structure, like a geosynthetic mat, that has dimensions in the longitudinal direction and in the transverse direction that are several times greater than its thickness. Geosynthetic mats and geosynthetic tapes can in turn have dimensions, in particular in the longitudinal direction, that are several times greater than their dimensions in the transverse direction, i.e. the length is significantly greater than the width. Typically, geosynthetic mats and geosynthetic tapes are therefore transported in a rolled-up or folded state and subsequently unfolded or spread out at the loading site so that the geosynthetic mats and geosynthetic tapes can be laid according to length. In the context of the invention, a geosynthetic mat is to be distinguished from a geosynthetic tape in that a geosynthetic mat has a plurality of plies, whereas a geosynthetic tape can also have only one single ply, but can also be constructed in multiple layers if necessary.
[0064] The geosynthetic tape according to the invention is characterized in that the geosynthetic tape is composed of fibers having a structure of at least two layers or has such fibers. The fibers have a fiber core bundle and a fiber core bundle sheath covering the fiber core bundle. The fiber core bundle and the fiber core bundle sheath are composed of two different biodegradable materials, which have different biodegradation rates from each other, i.e., biodegrade in such a way that under the same biodegradation conditions, the first material biodegrades faster or slower than the second material. Preferably, the second material has a biodegradation rate that is lower than the biodegradation rate of the first material, i.e., the second material biodegrades more slowly than the first material.
[0065] As described above in connection with a geosynthetic mat which can also have fibers or layers made of fibers in this way in at least two layers, this fiber configuration can achieve a more favorable course of mechanical strength during the biodegradation of the fibers or layers made of fibers, in particular in such a way that the fibers retain a high mechanical strength over a longer period of time in a first phase, i.e. during the biodegradation of only the fiber core sheath, and then, after the degradation of the fiber core sheath is complete, the mechanical strength of the fibers decreases rapidly in a second phase when the fiber core is degraded. It is understood that the properties explained above with reference to geosynthetic mats and also other improvements thereto can also be applied to geosynthetic strips and reference is made thereto accordingly.
[0066] According to a preferred embodiment, it is proposed that the fibers are present in the ply as a disordered structure, in particular as a nonwoven layer, or as an ordered structure, in particular as a knitted, woven or crocheted textile layer. Thus, the special fibers of the geosynthetic tape can be present as a disordered structure, for example as a nonwoven layer, from which the properties and advantages described above are derived, which are also produced in combination with the geosynthetic mat described above. Alternatively, the fibers can also be processed into an ordered structure, i.e. knitted, woven or crocheted or arranged in an aligned manner in another way, wherein an ordered structure is to be understood as follows: the structure has a regularly repeating geometric pattern of the direction of the fibers, typically a regularly repeating geometric pattern in the direction of a straight line or the intersection of two straight lines. With regard to the ordered structure, reference is also made to the properties and advantages described above for the geosynthetic mat.
[0067] The geosynthetic tape can then be further improved in that the fibers are coated with a fiber core sheath on the circumferential side and the end side, in particular in that the ply is produced in a process in which a fiber core ply is produced from a fiber core in a first step and in a subsequent second step the fiber cores of the fiber core ply are coated with a sheathing material. This embodiment of coating the fiber core with a fiber core sheath on the circumferential side and the end side can be achieved in particular in that the ply is first produced from the fiber core, i.e., processed into a nonwoven or woven, knitted or crocheted, and then the ply produced in this way, consisting of the fiber core, is coated with a fiber core sheath, for example by immersion in a liquid or by wetting with a liquid in a spraying or coating method, so that the fibers are coated on all sides. In order to achieve the biodegradable properties in the desired manner, this is advantageous and is therefore preferred to a method in which the fibers are completely preproduced and subsequently processed, since in this processing method the fiber core bundle cross-section ends at the end sides are exposed due to the necessary separation of the fibers, so that rapid biodegradation can be achieved.
[0068] Another aspect of the invention is a geosynthetic mat of the structure and function described above, wherein the upper and / or lower covering layer has or is formed by a geosynthetic tape of the structure and function described above. As described above, the properties of such a geosynthetic tape with two layers of fibers contained therein can be used particularly advantageously for a geosynthetic mat according to the invention.
[0069] Another aspect is the use of a geosynthetic mat of the above-described construction or a geosynthetic tape of the above-described construction for producing a sealing layer in soil or at the bottom of a body of water. As already explained above, the geosynthetic mat according to the invention and the geosynthetic tape according to the invention are particularly suitable for producing sealing layers in soil and, moreover, at the bottom of a body of water. Here, the balanced properties of the mechanical peel strength of the first phase of swelling of the intermediate filling layer work particularly well and a safe seal can be achieved, whereas the environmental load in the case of degradation of the geosynthetic mat or geosynthetic tape or in the case of discharge of parts of the geosynthetic mat or tape due to erosion can be significantly reduced or completely avoided by the biodegradation of the cover layer and the connecting structure and, if applicable, the additional barrier layer.
[0070] The use is advantageously improved in that the geosynthetic mat is unrolled in a first step and in a subsequent second step the geosynthetic mat is impregnated with a liquid, in particular with a hard oil. In the use method described, the geosynthetic mat or geosynthetic tape is first almost completely prefabricated by producing layers, arranging the layers relative to one another and connecting them to one another, and then rolling up the geosynthetic mat or tape prefabricated in this way so that it can be transported. Subsequently, after the transport to the installation site has been completed, the geosynthetic mat or tape is unrolled in order to be laid therefrom and then wetted at the installation site with a liquid that influences the further mechanical and / or biological behavior. By carrying out the impregnation of the geosynthetic mat or tape only at a second moment following the production of the geosynthetic mat or tape, it is avoided that the properties of the geosynthetic mat or tape could be changed during possible storage or transportation due to the impregnation with liquid that has already occurred, and it is achieved that the desired functional and structural property effects caused by the liquid only begin at the installation site after wetting with liquid at the installation site.
[0071] It should be understood here that the impregnation can also consist in the covering of a fiber core bundle, which is processed into a covering layer, a connecting structure, etc. in a geosynthetic mat or tape during pre-production and is subsequently provided with an additional coating on site in order to favorably influence the biodegradation behavior and the mechanical properties.
[0072] The wetting / impregnation can be carried out in particular in such a way that the wetting / impregnation is selected as a function of the environmental conditions measured beforehand at the installation site, for example by adapting the layer thickness to these environmental conditions or by selecting the liquid with which the impregnation is carried out from a plurality of different liquids available or by mixing them. Environmental conditions that can influence the selection or the intensity of the impregnation are, for example, the moisture content of the soil, the pH value of the soil, the concentration of substances in the soil which accelerate or slow down biodegradation processes, the intensity of the UV radiation at the installation site and other influencing factors. In principle, it is to be understood that in the case of the type of use described with pre-wetting, the point in time from which the swelling-degradation ratio is determined and lies within the mentioned range should be determined from the time of impregnation of the geosynthetic mat, even if the liquid with which the impregnation is carried out may not have yet triggered biodegradation.
[0073] According to a further preferred development of the use according to the invention, it can be provided that the geosynthetic mat is impregnated with a liquid at a first point in time before laying, the liquid causing pre-swelling of the intermediate filling layer and that it is installed at a second point in time at the installation site into the installation position and then swells in the installation position by supplying liquid, in particular from the surrounding soil. According to this embodiment, it is provided that the geosynthetic mat or strip is already impregnated with a liquid before its laying, the liquid causing pre-swelling of the intermediate filling layer. Pre-swelling is to be understood as limited swelling, wherein the material of the intermediate filling layer has not yet utilized its maximum swelling capacity, i.e. has not yet expanded to the maximum extent, but has only utilized a portion of said swelling capacity. This impregnation with liquid for the pre-swelling can be carried out, for example, already during the production of the geosynthetic mat or strip, but can alternatively also be carried out in such a way that the geosynthetic mat is produced at a first point in time and impregnated for pre-swelling at a second point in time, for example shortly before the geosynthetic mat is delivered or transported to the installation site, so that the effects of changes in the geosynthetic mat during a possible storage period between the time of production and the time of transport are thereby avoided. Pre-swelling can be promoted in a beneficial way and can be used to positively influence the initial swelling behavior of the geosynthetic mat directly after installation in the first days or weeks, so as to avoid disadvantageous structural changes or changes in the mechanical properties.
[0074] The liquid with which the geosynthetic mat is impregnated at the first moment can correspond to or be similar to the liquid with which swelling is also caused at the installation site, i.e., for example, by impregnation with water. However, in other applications, the liquid with which the impregnation is carried out at the first moment can also be different from the liquid with which the geosynthetic mat is wetted at the installation site, i.e., in particular, have a different composition or contain additives that promote preswelling, which also act, for example, in such a way that preswelling is promoted, but biodegradation is hindered or prevented, in order to prevent premature biodegradation of the cover layer and the connecting structure due to the impregnation at the first moment.
[0075] It is then preferably provided that the geosynthetic mat is placed in a transportable state after the impregnation at the first time, in particular rolled up or folded for this purpose, and can then be transported to the installation site. In principle, it is preferred to carry out the impregnation of the geosynthetic mat before the transportable state is established in order to achieve a uniform impregnation at the first time, in order to avoid different impregnations of the geosynthetic mat in a spatially resolved manner.
[0076] The use according to the invention can be further improved with respect to the use of a geosynthetic mat for producing a sealing layer at the bottom of a body of water or with respect to the use of a geosynthetic mat for producing a seal in a soil layer, in that the geosynthetic mat is first laid on the bottom of the body of water or introduced into the region of the bottom of the body of water or into the soil layer, and wherein the upper cover layer of the geosynthetic mat has open porosity, and as a further improvement, the outer surface of the upper cover layer has a rough structure pointing outwards, and the geosynthetic mat is laid on the bottom of the body of water so that the outer surface of the upper cover layer points upwards, and wherein in addition, the intermediate filling layer has a thickness of 1×10 -5 Up to 1×10 -9 m / s, and particles carried above the water body in the water body are trapped in the pore structure and are further advantageously affected by the reduced flow velocity and reduced drag stress due to the rough structure, and migrate through the upper cover layer into the middle fill layer, so that particles from the water body accumulated in the middle fill layer and the upper cover layer form a sealing layer, which forms a supplementary sealing effect in the expanded middle fill layer and an additional sealing layer at the site of the degraded upper cover layer at a second moment after the biodegradation of the upper cover layer.
[0077] According to the advantageous use, the geosynthetic mat is used in such a way that the middle filling layer first has a certain permeability value within a defined range of values, so that liquids can pass through. The permeability, combined with the open porosity and thus the permeability of the upper covering layer and preferably also the lower covering layer, is also improved by a rough structure of the outer surface of the upper covering layer, which is directed outwards, and which can be provided, for example, by the typical roughness of a nonwoven layer or by an ordered structure of the covering layer, which is established by weaving, crocheting or knitting. It is achieved that the middle filling layer is flowed through by liquid in a first phase after installation, and particles in the liquid can be fixedly attached in the middle filling layer and the upper or lower covering layer, thereby reducing the permeability. Therefore, the flow through and the associated fixed attachment of particles in the flowing liquid in the geosynthetic mat cause a gradual sealing of the geosynthetic mat in the first phase after installation, which seal is continuously transformed into a state in which the permeability is reduced to such an extent that flow through hardly or no longer occurs, and the geosynthetic mat is sealed at this time. The sealing effect caused by the particles at the installation site during the first phase is known as so-called silting and can be used advantageously for overall properties, in particular by constructing the geosynthetic mat. Thus, due to the construction of the geosynthetic mat in the described manner and the use of silting, it is not necessary for the intermediate filling layer to expand significantly and to have to work with a high counterpressure against the swelling behavior within the geosynthetic mat, so that the desired sealing is provided only by the swelling behavior. This reduces the requirements for the peel strength of the upper and lower cover layers and the connecting structure and also makes it possible to design the intermediate filling layer so that it has only limited swelling behavior, i.e., for example, also to provide the intermediate filling layer with additives that increase the shear strength of the intermediate filling layer. Thus, the design and use according to the invention allow the provision of an intermediate filling layer with increased shear strength, reduce the mechanical requirements for the upper and lower cover layers and the connecting structure, also in terms of their biodegradation behavior and the resulting peel strength, and still achieve very low penetration in the long-term use of the geosynthetic mat.
[0078] It is particularly preferred that the use is carried out in such a way that the amount of particles carried in the water body per water volume is determined as the particle mass density before the geosynthetic mat is laid on the bottom of the water body, and the geosynthetic mat is designed so that the swelling-degradation ratio and / or the degree of residual peel strength and / or the thickness of the upper covering layer are designed in a manner dependent on the particle mass density, in particular, the higher the particle mass density, the lower the swelling-degradation ratio, the greater the degree of residual peel strength and / or the smaller the thickness of the upper covering layer. According to the embodiment, before the geosynthetic mat is installed, the properties of the water body, in particular the amount of particles carried in the water body per water volume, i.e. the particle density in the water body, are determined. This can include the number of particles, but can also alternatively or additionally include the size of the particles carried in the water body. The geosynthetic mat is then formed in accordance with the determined characteristic values of the body of water regarding the amount of particles, wherein the adapted formation can consist in adjusting the properties of the upper cover layer and / or the properties of the intermediate filling layer in order to achieve an ideal silting effect and to ideally adapt the geosynthetic mat thereto. Thus, in water bodies in which a particularly high number of particles is carried, an intermediate filling layer with a lower swelling bulge can be used in the geosynthetic mat than in water bodies with only a low particle density. The properties of the upper cover layer can be adjusted in the same way, i.e., for example, in water bodies with a high particle density, a faster biodegradation with a correspondingly high reduction in peel strength can also be used, since in this case the rapid sealing effect caused by the silting effect is taken into account, so that the counterpressure against the expansion of the intermediate filling layer is not as important as in water bodies with a low particle concentration, which require such swelling behavior for a good sealing effect of the geosynthetic mat. Furthermore, the surface of the cover layer can be adjusted with regard to the roughness structure so that, depending on the specific flow conditions of the water body and the drag stresses at the surface of the mat, particles can be reliably accumulated and embedded in the mat.
[0079] Another aspect of the invention is a method for producing a geosynthetic mat, the method comprising the following steps: providing a first geosynthetic layer; applying an intermediate filling layer consisting of a filling layer material including a swellable material to the first geosynthetic layer, wherein the filling layer material has swelling properties; laying a second geosynthetic layer on the intermediate filling layer; connecting the first geosynthetic layer to the second geosynthetic layer through the intermediate filling layer by means of a connecting structure, in particular by needle punching, wherein a layer consisting of a first biodegradable material is provided as the first geosynthetic layer and a layer consisting of a second biodegradable material is laid on as the second geosynthetic layer, wherein the upper covering layer and the lower covering layer have a connection to each other characterized by a peel strength through the connection, wherein the connection is characterized by a degree of residual peel strength at a predetermined time after the start of the biodegradation process, and the degree of residual peel strength is reduced by reducing The invention relates to a method for preparing a geosynthetic mat according to the present invention, wherein the geosynthetic mat has a peel strength which is formed by the square of a quotient of a peel strength of 0.05% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.07% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.08% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.05% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.05% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.08% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.05% and an initial peel strength of 0.06% compared to the square of a quotient of a peel strength of 0.08% and an initial peel strength of 0.06% and an initial ...6% and an initial peel strength of 0.08% and an initial peel strength of 0.06% and an initial peel strength of 0.06% and an initial peel strength of 2 The method is characterized in that the swelling-degradation ratio formed by dividing the swelling bulge by the residual peel strength is within a range of 1 to 5 within the first week after the simultaneous start of the swelling process and the biodegradation process and within a range of 1.5 to 25 at each predetermined time from the second month to the end of the third month after the start of the swelling and degradation, preferably within a range with a lower limit of 2 and / or an upper limit of 15.
[0080] With regard to the production method it is understood that the properties of the geosynthetic mat with regard to the degree of residual peel strength and swelling elevation and the swelling-degradation ratio resulting therefrom may develop over time and depending on its height as explained above with regard to the geosynthetic mat.
[0081] Furthermore, the production of the specific rough structure of the surface can be carried out by laying a structural material having a degradation behavior corresponding to that of the first or second covering layer or a third degradation rate and needle-punching the structural material with the geosynthetic layer. The method according to the invention can be used in particular for producing a geosynthetic mat having the properties described above and allows providing a geosynthetic mat suitable for the use described above at the installation site.
[0082] It is to be understood that the steps performed in the method preferably lead to the structural and functional properties and advantages of the geosynthetic mat according to the invention explained above and enable the use explained above. In this regard, reference is made to the above explanation of the corresponding properties and advantages with regard to the method steps.
[0083] Here, the method described above and the improvement of the method described above according to the invention can preferably be improved so that the first biodegradable material and / or the second biodegradable material are formed in the form of fibers, in particular as fibers having a fiber core bundle consisting of the first biodegradable material and a fiber core bundle sheathing consisting of the second biodegradable material, wherein the first biodegradable material has a first biodegradation rate, which is higher than the second biodegradation rate of the second biodegradable material. According to the method improvement, the first biodegradable material and / or the second biodegradable material are formed by fibers of a two-layer structure, i.e. having a fiber core bundle and a fiber core bundle sheathing, wherein the fiber core bundle sheathing can already exist before the corresponding layer or connecting structure is manufactured from the fibers, or can be applied subsequently in the production method, or can also be applied on site at the installation site. In this regard, reference is made to the above explanation of the use of the corresponding fibers in the geosynthetic mat or the corresponding geosynthetic tape according to the invention.
[0084] The method can be further improved in that in a first step, a first covering layer and / or a second covering layer are produced from the fiber core bundle, and in a subsequent second step, the fiber core bundle is covered with a fiber core bundle covering in the first covering layer and / or the second covering layer. According to the improved solution, the fiber core bundle covering is applied only after the covering layer is produced from the fiber core bundle, so that the fiber core bundle is fully covered, also at the possible end-side cut edges. In this regard, reference is also made to the above description.
[0085] It is further preferred that the upper and / or lower covering layers, the intermediate filling layer or the entire geosynthetic mat is impregnated with a liquid, in particular a hardening liquid, such as a hard oil. The production step of impregnation with a liquid, such as a hard oil, can again be carried out directly at the production site during the production of the geosynthetic mat, but can also be carried out later, i.e., for example, directly before or after the transport of the geosynthetic mat to the installation site, for example already in the laid geosynthetic mat. In this regard, the advantages of the time-staggered impregnation with a liquid explained above also apply to the method according to the invention.
[0086] Furthermore, it is preferred that a non-swellable additional material, in particular sand, is additionally applied when applying the intermediate filling layer. By applying the non-swellable additional material, on the one hand, the swelling behavior of the intermediate filling layer can be influenced, for example, in order to promote the silting effect, and on the other hand, the shear strength of the intermediate filling layer can be increased, thereby improving the suitability of the geosynthetic mat for installation in shear load situations, for example, installation on slope layers, which has an advantageous effect in particular after the biodegradation of the upper and lower covering layers and the connecting structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] The preferred embodiments of the present invention are described with reference to the accompanying drawings. The accompanying drawings show:
[0088] Figure 1 shows a schematic, perspective and partially cutaway view of a geosynthetic mat according to the invention and fanned out according to the plies,
[0089] Figure 2 shows a transversely sectioned longitudinal view of a second embodiment of a geosynthetic mat according to the invention,
[0090] Figure 3 A perspective cut-away view showing fibers for producing a geosynthetic mat according to the invention,
[0091] Figure 4 A second embodiment of a fiber for producing a geosynthetic mat according to the invention is shown in a longitudinally sectioned side view.
[0092] Figure 5 A diagrammatic representation of the time course of the peel strength and swelling of a geosynthetic mat according to the invention is shown. DETAILED DESCRIPTION
[0093] First refer to Figure 1A preferred embodiment of the geosynthetic mat according to the invention is constructed from a total of five layers. The uppermost layer is a first sealing layer 10, which is made of a biodegradable synthetic material as a liquid-tight film and covers the upper surface of the geosynthetic mat as a fluid barrier.
[0094] An upper covering layer in the form of a nonwoven layer 20 is arranged below and adjacent to the upper sealing layer 10. The nonwoven layer is constructed from randomly laid fibers and typically has a thickness that is greater than the sealing layer 10, in particular three to ten times greater than the thickness of the sealing layer 10.
[0095] Below the upper cover layer 20 and adjacent thereto, an intermediate filling layer in the form of a layered silicate layer consisting of sodium bentonite is arranged. The thickness of the intermediate filling layer 30 is greater than the thickness of the nonwoven layer 20, typically 5 to 20 times the thickness of the nonwoven layer 20. The intermediate filling layer is composed of a mixture of sodium bentonite particles and sand particles, and can be impregnated due to application, such as impregnation with linseed oil. Through the composition, the intermediate filling layer can initially have basic strength and groundwater impermeability, and the strength and water impermeability are further improved by swelling of the sodium bentonite in the component with the help of surrounding moisture, such as soil moisture. The sodium bentonite is converted into calcium bentonite by the swelling process, which causes the curing of the intermediate filling layer. It should be understood that the intermediate filling layer can also be composed in other ways, and then also has an initial basic strength and initial basic tightness that can be improved by swelling from the surrounding moisture. Therefore, for example, the middle filling layer can only be composed of swellable materials, such as bentonite or phyllosilicate, or it is also possible to use additives different from sand. The impregnation with linseed oil can be replaced or supplemented by other liquids, such as hard oil, or this impregnation can be omitted.
[0096] A second sealing layer 40 is arranged below the middle filling layer 30 and is formed identically to the first sealing layer 10. The first sealing layer 10 and the second sealing layer 40 prevent the active substances that accelerate or inhibit swelling from entering the middle filling layer from the surrounding soil layer directly after the geosynthetic mat is installed, thereby adversely affecting the swelling behavior.
[0097] Finally, a geotextile layer 50 consisting of woven fibers is arranged below and adjacent to the second sealing layer 40. The fibers in the geotextile layer 50 are thus oriented relative to one another in an ordered manner, here in a rectangular grid pattern, and ensure good longitudinal and transverse load capacity of the geosynthetic mat.
[0098] The entire geosynthetic mat is fixed relative to one another in the thickness direction, i.e. perpendicularly to its longitudinal and transverse extension, by the needling 11. The needling fixing comprises a plurality of individual needlings which are distributed in a planar manner over the entire geosynthetic mat and can be arranged, for example, in rows and columns or pseudo-randomly relative to one another. The needling connects the upper cover layer to the lower cover layer in a planar manner, so that the composite consisting of the upper and lower cover layers and the needling has a resistance to peeling off of the upper or lower cover layer from the composite, i.e. a peel strength.
[0099] The needling can be produced in terms of production technology by piercing the geosynthetic mat vertically with barbed needles, thereby taking fibers from the nonwoven layer 20 and / or the geotextile layer 50 and pulling them vertically through the geosynthetic mat. The fibers are hooked in the geotextile layer 50 and the nonwoven layer and can also be hooked in the sealing layers 10 and 40. The hooking and wrapping can be additionally reinforced by welding or knotting in order to strengthen the fastening by the needling. Instead of such needling, other methods of fixing the layers in the geosynthetic mat to one another can also be used, for example the geosynthetic mat can be sewn, for example by sewing with the fibers in the same pattern as the needling, thereby guiding the sewing thread vertically through the geosynthetic mat at multiple points, thereby fixing and stabilizing the layers relative to one another. For use in canals and water bodies with silting effects, the layer 10 can be replaced by a rough surface structure and the layer 40 can be omitted in order to achieve an initial flow-through.
[0100] It will be understood that the geosynthetic mat extends in the longitudinal direction LR and in the transverse direction QR and can in particular be rolled up along the longitudinal direction LR. The edges of the geosynthetic mat can be sealed in such a way that the first sealing layer 10 and the nonwoven layer 20 as well as the lower sealing layer 40 and the textile layer 50 protrude laterally beyond the intermediate filling layer when viewed in the transverse direction, and the protruding regions are sewn together in order to also laterally surround the intermediate filling layer.
[0101] Figure 2 A second embodiment of a geosynthetic mat according to the invention is shown in a transversely sectioned longitudinal view. Here, the middle filling layer 130 is also arranged centrally. A first sealing layer 110 and a second sealing layer 140 are arranged adjacent to the middle filling layer above and below, respectively, so that Figure 1Unlike the first embodiment of the present invention, the first and second sealing layers are placed directly adjacent to the middle filling layer. A nonwoven layer 120 is then arranged above the first sealing layer as an upper covering layer, and a textile layer 150 is arranged below the second sealing layer 140 as a lower covering layer. The individual layers of the geosynthetic mat are in turn fixed and fastened relative to one another by the needling 111; it can also be seen that the upper covering layer, the first sealing layer, the second sealing layer and the lower covering layer protrude laterally in the transverse direction and are sewn or needled to one another along the side edges in order to also laterally close the middle filling layer.
[0102] Figure 3 Fibers are shown, and a connecting structure, for example a connecting structure as a needle-punched part 11, a nonwoven layer 20, 120 or a fabric layer 50, 150 can be composed of the fibers, or the fibers can be included in these layers. The fibers include a fiber core bundle 210 composed of a first biodegradable material. A fiber core bundle sheath 220 is arranged around the fiber core bundle as a cylindrical sheath, which is composed of a second biodegradable material. Compared with the second biodegradable material, the first biodegradable material has a higher strength and a faster biodegradation rate. If the fiber constructed in two layers is provided to a biodegradation process and at the same time should also absorb mechanical loads in a limited period of time, a favorable variation curve of the mechanical load capacity of the fiber is obtained here. In the variation curve, the mechanical load capacity is initially only slightly reduced or not reduced at all, because only the fiber core bundle sheath is biodegraded, and the fiber core bundle sheath does not make a decisive contribution to the mechanical properties. After the fiber core bundle coating 220 is degraded, the fiber core bundle 210 is subsequently degraded, which causes a subsequent rapid decrease in the mechanical strength of the fiber.
[0103] Figure 4 1 shows a longitudinally sectioned side view of a short fiber or medium-length fiber according to the present invention. The fiber also comprises a fiber core bundle 310, which is covered by a fiber core bundle covering 320. The fiber core bundle and the fiber core bundle covering 310, 320 are similar in mechanical properties and biodegradation rate to those described above according to the invention. Figure 3 The embodiment of the present invention is constructed in a similar manner. Figure 4 As can be seen in FIG. 3 , the fiber core bundle sheath 320 surrounds the fiber core bundle 310 all around, that is, also at the end. This is achieved by applying the fiber core bundle sheath only after processing and cutting the fiber core bundle 310 , thereby achieving a surrounding sheath that is beneficial for biological and mechanical degradation behavior.
[0104] Figure 5 The variation curve of the peel strength S(t) of a composite body consisting of two nonwoven fabric layers needle-punched with each other is shown schematically. Figure 3 or Figure 4 The fiber structure of the composite body comprises or consists of a fiber having a fiber core bundle and a fiber core bundle sheath. As can be seen from the trend of the curve, the curve initially only slightly decreases in the first time period, which therefore corresponds to only a small decrease in tensile strength. Subsequently, at the moment t when the fiber core bundle sheath is substantially completely biodegraded, the peel strength of the composite body decreases more steeply, because from the moment t, the fiber core bundle biodegrades, so that the peel strength of the fiber, which is decisively affected by the fiber core bundle, decreases. In the embodiment described, the peel strength of the composite body is affected as a whole by the biodegradation of the fibers in the upper and lower covering layers and the connecting structure, i.e., the needle-punched part. It should be understood that in other composite systems, independent degradation performance may also decisively or individually affect the decrease in peel strength, for example, when a non-biodegradable connecting structure connects two covering layers to each other, then one or both of the covering layers are biodegradable, and the connection can be achieved, for example, by suturing. In the case described, the peel strength is only affected by the anchoring strength of the connecting structure in the biodegradable covering layer.
[0105] exist Figure 5 The swelling behavior of the intermediate filling layer is also shown in the form of a curve Q(t) as the swelling ridge of the intermediate filling layer. As can be seen, the volume of the intermediate filling layer first increases rapidly after a short delay at the beginning, which corresponds to a rapid initial swelling, so as to then turn into a slower volume increase corresponding to a slower swelling, which then gradually approaches the final swelling state.
[0106] from Figure 5 It can also be read that a geosynthetic mat having a layer made of fibers as an upper and lower covering layer, which will have a peel strength behavior according to S(t) and which will also be needled with such fibers, will still have a high peel strength during the decisive part of the swelling of the intermediate filling layer through the intermediate filling layer having a swelling behavior according to Q(t), so that it is possible to counteract the swelling pressure with a sufficiently high counterpressure in order to achieve the desired good homogenization and to remove the pores of the intermediate filling layer by swelling. Only after the swelling has essentially ended and the volume and weight of the intermediate filling layer have only slightly increased due to the residual swelling, the upper and lower covering layers and the biodegradable fibers of the needled portion are in a phase of rapid biodegradation and thus rapid reduction of the peel strength, i.e., in a high degree of peel strength reduction. At this point in time, it is no longer necessary to apply a decisive counterpressure to resist the swelling, but the geosynthetic mat then benefits from the intermediate filling layer, which has already swelled in a beneficial manner and has a sealing effect.
[0107] The calculation of the swelling-degradation ratio is described in detail below based on four examples:
[0108] 1.) The volume of the intermediate filling layer that expands under a load of 45 Pa in the swelling test is 40 liters after a swelling time of one week and 50 liters after three months. The volume before the start of swelling is 20 liters. This results in a doubling of the volume within one week, i.e. a swelling swelling of 2 and a swelling swelling of 2.5 after three months; the peel strength at the beginning of the composting test is 120 N / 10 cm, which remains approximately unchanged in the first week and 90 N / 10 cm after three months of composting. This results in a 25% reduction in the peel strength after three months, i.e. a residual peel strength of 0.56. This results in a swelling-degradation ratio of 2 after one week and a swelling-degradation ratio of 4.4 after three months.
[0109] 2.) The volume of the intermediate filling layer that expanded under a load of 45 Pa in the swelling test was 60 liters after a swelling time of one week, 80 liters after three months and then no longer increased significantly. The volume before the start of swelling was 20 liters. This resulted in a volume that tripled in one week, i.e. a swelling swelling of 3 and a swelling swelling of 4 after three or more months; the peel strength at the beginning of the composting test was 120 N / 10 cm, which decreased to 115 N / 10 cm in the first week, the peel strength after three months of composting was 60 N / 10 cm and decreased to 40 N / 10 cm until the twelfth month. This resulted in a residual peel strength level that decreased by about 4% to 0.96 in the first week, a peel strength decrease of 50% after three months, i.e. a residual peel strength level of 0.25, and a residual peel strength level of 0.1 after twelve months. This results in a swelling / degradation ratio of 3.1 after one week, which increases to 16 after three months and to 36 after twelve months.
[0110] 3.) The volume of the intermediate filling layer expanded under a load of 45 Pa in the swelling test after a swelling time of one week is 30 liters, after three months it is 40 liters and after twelve months it is also 40 liters. The volume before the start of swelling is 20 liters. This results in a swelling degree of 1.5 after one week and a swelling degree of 2 after three and twelve months; the peel strength at the beginning of the composting test is 120 N / 10 cm, which remains approximately unchanged in the first week, and after three months of composting it is 90 N / 10 cm and drops to 60 N / 10 cm until the twelfth month. This results in a residual peel strength of 0.56 after three months and a residual peel strength of 0.25 after twelve months. This results in a swelling-degradation ratio of 1.5 after one week, which increases to 3.6 after three months and to 8 after twelve months.
[0111] 4.) The volume of the intermediate filling layer expanded under a load of 45 Pa in the swelling test after a swelling time of one week is 40 liters, after three months it is 60 liters and after twelve months it is 80 liters. The volume before the start of swelling is 20 liters. This results in a swelling swelling of 2 after one week, a swelling swelling of 3 after three months and a swelling swelling of 4 after twelve months; the peel strength at the beginning of the composting test is 120 N / 10 cm, which decreases to 110 N / 10 cm in the first week, the peel strength after three months of composting is 40 N / 10 cm and decreases to 20 N / 10 cm until the twelfth month. This results in a residual peel strength of 0.84 after one week, a residual peel strength of 0.11 after three months and a residual peel strength of 0.03 after twelve months. This results in a swelling / degradation ratio of 2.4 after one week, which increases to 27 after three months and to 133 after twelve months.
[0112] Thus, in the examples in this context, Examples 1, 2 and 3 are geosynthetic mats having particularly preferred properties according to the invention and achieving good sealing behavior. The geosynthetic mat according to Example 4 has a rapid swelling behavior with respect to rapid biodegradation and an accompanying loss of peel strength, which, although it is still possible to achieve good sealing behavior under strong loads by the soil layer located above, is not so well suited if there is no such weight load to compensate for the rapid biodegradation, because there is then too little swelling counterpressure to achieve a good seal.
Claims
1. A geosynthetics mat, comprising: - upper covering layer, - lower covering layer, - an intermediate filling layer composed of a filling layer material arranged between the upper cover layer and the lower cover layer, the filling layer material comprising a swellable material, wherein the filling layer material has swelling behavior, - a connecting structure, by means of which the upper cover layer and the lower cover layer are mechanically connected to each other at a plurality of locations through the intermediate filling layer, wherein the locations of connection are spaced apart from each other, preferably are locations following each other along a straight line at regular intervals, so that the upper cover layer and the lower cover layer have peel strength with each other via the connecting structure, Characterized in that the upper covering layer and / or the lower covering layer consists of or includes a biodegradable material, - wherein the peel strength is characterized at a predetermined time after the start of the biodegradation process by a residual peel strength degree, which is formed by the square of the quotient of the reduced peel strength and the initial peel strength, the upper and lower covering layers and the connecting structure having the reduced peel strength at the predetermined time, the upper and lower covering layers and the connecting structure having the initial peel strength before the start of the biodegradation process, wherein o in a composting test by placing the geosynthetic mat completely in fertilizer and composting in a temperature range of above 25° C. and below 65° C. until the predetermined time, and in a peeling test by measuring the peel strength before the placing and after removal from the fertilizer at the predetermined time, or o in a marine incubation test with the following environmental conditions: temperature 30°C + / - 2°C; aerobic conditions in seawater with a salinity of 3.5 wt.% + / - 1 wt.%, and in a peel test the peel strength was measured at the predetermined times before the insertion and after removal from the seawater; To obtain the residual peel strength, and wherein the swelling behavior is characterized by a swelling ridge, which is formed by the quotient of the volume of the filling layer material together with the water absorbed therein at the predetermined time and the initial volume of the filling layer material before the start of swelling, wherein the swelling ridge is obtained by completely immersing the filling layer material layer in a water pool and loading the filling layer material layer with 4.5 N / m 2 to obtain it under pressure, The swelling-degradation ratio formed by dividing the swelling ridge degree by the residual peel strength degree is within the range of 1 to 5 within the first week after the swelling process and the biodegradation process start simultaneously, and is within the range of 1.5 to 25 from the second month to the end of the third month after the swelling and degradation start, preferably within the range with a lower limit of 2 and / or an upper limit of 15.
2. The geosynthetic mat according to claim 1, It is characterized in that The swelling-degradation ratio is within a range between 2 and 50, preferably within a range with a lower limit of 3 and / or an upper limit of 30, from the third month to the end of the twelfth month after the start of the swelling process and the biodegradation process.
3. A geosynthetic mat according to any one of the preceding claims, It is characterized in that - the swelling degree is greater than 1.25 one week after the swelling process begins, and / or - the swelling degree is greater than 1.5 one month after the start of the swelling process, and / or - the residual peel strength level is less than 0.95 three months after the start of the swelling process, and / or - the residual peel strength level is less than 0.75 twelve months after the start of the swelling process.
4. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The connection structure includes a needle-punched portion between the upper cover layer and the lower cover layer or is formed by such a needle-punched portion.
5. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The upper covering layer and / or the lower covering layer and / or the connecting structure comprise fibers composed of a biodegradable material or are formed by such biodegradable fibers.
6. A geosynthetic mat according to any one of the preceding claims, It is characterized in that - the biodegradable materials of the upper covering layer and the lower covering layer are different from each other, or - The biodegradable material of the upper covering layer and the lower covering layer is identical.
7. A geosynthetic mat according to any one of the preceding claims, It is characterized in that - the biodegradable material of the connecting structure is different from the biodegradable material of the upper covering layer and / or the lower covering layer, or The biodegradable material of the connecting structure is consistent with that of the upper covering layer or the lower covering layer.
8. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The upper covering layer and / or the lower covering layer comprises a nonwoven layer composed of a biodegradable material or is formed by such a nonwoven layer.
9. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The upper covering layer and / or the lower covering layer comprises or is formed by an ordered textile layer, in particular a knitted, woven or crocheted textile layer, of a biodegradable material.
10. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The filling material comprises or is formed by a mixture of a swellable material, such as bentonite powder, in particular sodium bentonite, and a non-swellable additive, such as an inorganic bulk material, in particular sand, glass particles, chalk or coal particles.
11. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The intermediate filling layer comprises a hardening or hardening-inducing liquid, in particular, for example, a hard oil or wax or a varnish based on, for example, linseed oil or tung oil, wherein the liquid can also be present only in partial regions of the intermediate filling layer, such as partial cross sections.
12. A geosynthetic mat according to any one of the preceding claims, It is characterized in that An upper barrier layer arranged adjacent to the upper cover layer and / or a lower barrier layer arranged adjacent to the lower cover layer is provided, wherein each barrier layer is formed by a film, in particular by a film consisting of a biodegradable material, wherein preferably - the upper barrier layer is disposed between the upper cover layer and the intermediate filling layer, - the lower barrier layer is disposed between the lower cover layer and the intermediate filling layer, - the upper cover layer is disposed between the upper barrier layer and the intermediate filling layer, or - The lower cover layer is disposed between the lower barrier layer and the intermediate filling layer.
13. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The biodegradable material of the respective barrier layer and the biodegradable material of the upper cover layer or the lower cover layer adjacent to the film -same, or -different.
14. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The biodegradable material of the upper covering layer, the lower covering layer and / or the connecting structure includes or is composed of fibers, wherein the fibers have a fiber core bundle composed of a first biodegradable material and a fiber core bundle covering portion composed of a second biodegradable material covering the fiber core bundle, wherein the first biodegradable material has a first biodegradation rate, and the first biodegradation rate is higher than a second biodegradation rate of the second biodegradable material.
15. Geosynthetic mat according to the preceding claim, It is characterized in that The first biodegradable material comprises natural fibers, such as coconut fibers, jute fibers, hemp fibers, bamboo fibers or flax fibers, or biodegradable synthetic fibers composed of PBS, PBAT, PLA, or a polymer blend composed of at least two materials, or is composed of such materials, or the biodegradable material comprises a mixture of a fiber core composed of natural fibers and synthetic fibers, wherein preferably, the weight share of the synthetic fibers is greater than 30%, in particular greater than 50%.
16. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The second biodegradable material comprises or consists of cellulose based synthetic materials, starch blends, lyocell, succinic acid (PBS), biodegradable polyesters such as polybutylene adipate terephthalate (PBAT) or polylactic acid (PLA) or wax.
17. A geosynthetic mat according to any one of the preceding claims, It is characterized in that The intermediate filling layer is characterized by a 1×10 -5 Up to 1×10 -9 The penetration between m / s.
18. A geosynthetic tape comprising at least one ply, the ply comprising or being formed by fibres, It is characterized in that The fiber comprises a fiber core bundle composed of a first biodegradable material and a fiber core bundle covering portion composed of a second biodegradable material covering the fiber core bundle, wherein the first biodegradable material has a first biodegradation rate and the second biodegradable material has a second biodegradation rate, and the second biodegradation rate is different from, in particular higher than, the first biodegradation rate of the first biodegradable material.
19. The geosynthetic tape according to claim 17, It is characterized in that The fibers are in the ply - as a disordered structure, in particular as a nonwoven layer, or - as an ordered structure, in particular as a knitted, woven or crocheted textile layer.
20. A geosynthetic strip according to claim 18 or 19, It is characterized in that The fibers are covered on the circumferential side and the end side by the fiber core bundle covering, in particular by manufacturing the layer using a process in which a fiber core layer is manufactured from a fiber core bundle in a first step and the fiber core bundle of the fiber core layer is coated with a covering material in a subsequent second step.
21. A geosynthetic mat according to any one of claims 1 to 17, It is characterized in that The upper cover layer and / or the lower cover layer comprises a geosynthetic strip according to any one of claims 18, 19 or 20 or is formed by such a geosynthetic strip.
22. Use of a geosynthetic mat 1-21 according to any one of the preceding claims 1 to 21 for producing a sealing layer in soil or at the bottom of a body of water.
23. The use according to claim 22, It is characterized in that In a first step, the geosynthetic mat is unrolled and in a subsequent second step, it is impregnated with a liquid, in particular with an oil, preferably a hard oil or a resin or a varnish based thereon.
24. The use according to claim 22 or 23, It is characterized in that At a first point in time before laying, the geosynthetic mat is impregnated with a liquid which causes partial pre-swelling of the intermediate filling layer and is subsequently introduced into an installation position at a second point in time at the installation site and subsequently swells in the installation position by supplying liquid, in particular from the surrounding soil.
25. The use according to claim 24, It is characterized in that After the first time, the geosynthetic mat is brought into a transportable state, in particular rolled up, and transported to the installation site.
26. Use according to any one of claims 22 to 25 for producing a sealing layer at the bottom of a body of water, It is characterized in that The geosynthetic mat is laid on the bottom of the water body at a first moment, The upper cover layer of the geosynthetic mat has open porosity and the outer surface of the upper cover layer has a rough structure directed outward, and the geosynthetic mat is laid on the bottom of the water body so that the outer surface of the upper cover layer points upward, and The middle filling layer has a 1×10 -5 Up to 1×10 -9 m / s, and particles in the water body carried above the water body are trapped in the rough structure and migrate through the upper cover layer into the middle fill layer, so that particles from the water body accumulated in the middle fill layer and the upper cover layer form a sealing layer, and at a second moment after the biodegradation of the upper cover layer, the sealing layer forms a supplementary sealing effect within the expanded middle fill layer and forms an additional sealing layer at the location of the degraded upper cover layer.
27. The use according to claim 26, It is characterized in that Before the geosynthetics mat is laid on the bottom of the body of water, the amount of particles carried in the body of water per water volume is determined as a particle mass density, and the geosynthetics mat is constructed so that the swelling-degradation ratio and / or the residual peel strength degree and / or the thickness of the upper covering layer are constructed in correlation with the particle mass density, and in particular so that the higher the particle mass density, the greater the swelling-degradation ratio, the smaller the residual peel strength degree, and / or the smaller the thickness of the upper covering layer.
28. A method for manufacturing a geosynthetic mat, the method comprising the steps of: - providing a first geosynthetic layer, - applying an intermediate filling layer consisting of a filling layer material comprising a swellable material onto said first geosynthetic layer, wherein said filling layer material has swelling behaviour, - laying a second geosynthetic layer onto said intermediate filling layer, - connecting the first geosynthetic material layer and the second geosynthetic material layer through the intermediate filling layer by means of a connecting structure, in particular by a needle-piercing portion, It is characterized in that As the first geosynthetic layer, a layer of a first biodegradable material is provided and as the second geosynthetic layer a layer of a second biodegradable material is applied, wherein the upper and lower covering layers have a connection to one another via the connection which is characterized by a peel strength, the connection being characterized by a residual peel strength degree at the predetermined time after the start of the biodegradation process, the residual peel strength degree being formed by the square of the quotient of the reduced peel strength and the initial peel strength, the upper and lower covering layers and the connecting structure having the reduced peel strength at the predetermined time, the upper and lower covering layers and the connecting structure having the initial peel strength before the start of the biodegradation process, wherein in a composting test the residual peel strength degree is determined by completely placing the geosynthetic mat in fertilizer and composting in a temperature range of above 25° C. and below 65° C. until the predetermined time, and in a peeling test the peel strength is measured before the placing and at the predetermined time after removal from the fertilizer, The swelling behavior is characterized by a swelling ridge, which is formed by the quotient of the volume of the filling layer material together with the water absorbed therein at the predetermined time and the initial volume of the filling layer material before the start of swelling, wherein the swelling ridge is obtained by completely immersing the filling layer material layer in a water pool and loading the filling layer material layer with 4.5 N / m 2 of pressure to obtain, and The swelling-degradation ratio formed by dividing the swelling ridge by the residual peel strength is within a range between 1 and 5 within the first week after the swelling process and the biodegradation process are simultaneously started, and within a range between 1.5 and 25 within each predetermined time from the second month to the end of the third month after the start of swelling and degradation, preferably within a range with a lower limit of 2 and / or an upper limit of 15.
29. A method according to claim 28 or the preamble of claim 28, wherein a layer of a first biodegradable material is provided as a first geosynthetic layer and a layer of a second biodegradable material is applied as a second geosynthetic layer, It is characterized in that The first biodegradable material and / or the second biodegradable material are in the form of fibers, in particular fibers having a fiber core bundle consisting of the first biodegradable material and a fiber core bundle sheath consisting of the second biodegradable material, wherein the first biodegradable material has a first biodegradation rate, which is higher than a second biodegradation rate of the second biodegradable material.
30. The method according to claim 29, It is characterized in that The first covering layer and / or the second covering layer are manufactured from the fiber core bundle in a first step, and the fiber core bundle in the first covering layer and / or the second covering layer is covered with the fiber core bundle covering in a subsequent second step.
31. The method according to any one of claims 29 to 30, It is characterized in that The upper cover layer and / or the lower cover layer, the intermediate filling layer or the entire geosynthetic mat is impregnated with a liquid, in particular a hydrophobic liquid such as preferably oil, preferably with a hardened hydrophobic liquid such as hard oil or a varnish based thereon.
32. The method according to any one of claims 29 to 31, It is characterized in that When applying the intermediate filling layer, a non-swellable additional material, in particular sand, is additionally applied.
Citation Information
Patent Citations
Shroud for use in coffin or other burials has an intermediate layer containing a microbiocidal powder or granulate to prevent escape of viruses or other microorganisms
DE19956783A1
multi-layer sealing mat
DE60203517T2
Waterproof sealing mat, essentially composed of a supporting layer, and intermediate layer of expandable clay, and a covering layer
EP0278419B1
Low permeability coefficient sodium bentonite waterproof blanket and preparation method thereof
CN103660424A
Sodium-based bentonite waterproof carpet
CN104191742A